2017
DOI: 10.1515/ecce-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Novel PID Tracking Controller for 2DOF Robotic Manipulator System Based on Artificial Bee Colony Algorithm

Abstract: -This study presents a well-developed optimization methodology based on the dynamic inertia weight Artificial Bee Colony algorithm (ABC) to design an optimal PID controller for a robotic arm manipulator. The dynamical analysis of robotic arm manipulators investigates a coupling relation between the joint torques applied by the actuators and the position and acceleration of the robot arm. An optimal PID control law is obtained from the proposed (ABC) algorithm and applied to the robotic system. The designed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…For comparison purposes, we select the same control parameters to range as presented by ElKhateeb and Badr 30 and we define the control constraint to be MAE < 0.04636. MAE is given in (43): ElKhateeb and Badr 30 assume a 2-DOF arm with specifications of M 1 = 1 .1em kg, M 2 = 1 .1em kg for the masses of the 2-DOF arm, and l 1 = 1 .1em m, l 2 = 1 .1em m for the lengths of the two arms. In our approach, the lengths of the arms and the motors are defined as design variables for the optimizer.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison purposes, we select the same control parameters to range as presented by ElKhateeb and Badr 30 and we define the control constraint to be MAE < 0.04636. MAE is given in (43): ElKhateeb and Badr 30 assume a 2-DOF arm with specifications of M 1 = 1 .1em kg, M 2 = 1 .1em kg for the masses of the 2-DOF arm, and l 1 = 1 .1em m, l 2 = 1 .1em m for the lengths of the two arms. In our approach, the lengths of the arms and the motors are defined as design variables for the optimizer.…”
Section: Resultsmentioning
confidence: 99%
“…MATLAB R2019b is applied as the simulation platform to track the ideal curve trajectories by using the FETSM, the ETSM [27], the ESM [28] and PID [10] methods respectively. By comparing the error of position tracking of each joint, the effects of the trajectory tracking of the above four control methods are analyzed.…”
Section: Analysis On Trajectory Trackingmentioning
confidence: 99%
“…Guechi et al [5] did a comparative study between a MPC and Linear Quadratic (LQ) optimal control of a two-link robot arm, and the simulation results showed that the proposed MPC gave a better system performance then the LQ optimal control approach. Elkhateeb [6] developed a novel tuning methodology of a PID controller for trajectory tracking of a manipulator robot. The optimal gains of the PID controller are obtained by using a dynamic inertia weight artificial bee colony optimization algorithm.…”
Section: Related Workmentioning
confidence: 99%